POTENSI DEPOSIT WOLFRAM DI INDONESIA: STUDI KASUS TOBOALI - BANGKA SELATAN - Imelda Eva Roturena Hutabarat; Sabtanto Suprapto; Priatna Priatna; Maryono Maryono; Rudiyansah Rudiyansah (Jurnal Teknologi Mineral dan Batubara, 2023)
Bangka island is one of the islands in the Southeast Asian Tin Belt that makes Indonesia the largest tin (Sn) producer in the world. The carrier of wolframite is a by product mineral of the mineral tin (cassiterite). This study aims to study the presence and type of wolfram-as by product in the tin deposits on Bangka island. The research area was conducted on the eastern edge of Klabat Granite in Kepoh Village, Toboali District, South Bangka, at coordinates of 106o 31' 58" BT, 2o 56' 56 " LS. The result shows the presence of wolfram with grade of wolfram in veins reaching 8287 ppm. Wolfram was identified as an associated mineral in the tin mineralization system in Toboali along with rare earth metals (LTJ), molybdenum (Mo) and platinum (Pt). The results of analytical studies (UV, XRF, ICP OES, mineragraphy) on Toboali area minerals show the presence of wolfram in ores, concentrates, slag, and floor crusts. The identified wolfram minerals are wolframite (Fe.Mn)WO4 and scheelite (CaWO4) which are characterized through differences in properties such as color, fluorosence, magnetic, specific gravity and hardness values. The results obtained showed the presence of wolfram in Toboali area with wolfram content of 742 ppm in ore and also in the tin process, specifically in slag II of 1.02%. In addition, wolfram is indicated on the furnace floor and on the anode slime. Indonesia as one of the countries that owns wolfram minerals needs to continue the wolfram extraction process so that Indonesia receive the added value from its minerals.